Wiliam THE EFFECT OF WORKING CAPITAL TURNOVER, FIXED ASSET TURNOVER, AND INVERNTORY TURNOVER ON RETURN ON ASSETS (ROA) OF PHARMACEUTICAL COMPANIES LISTED IN INDONESIA STOCK EXCHANGE IN THE PERIOD OF 2012-2016 - wiliam wiliam (Akuntansi Prima, 2019)
This study aims to examine working capital turnover, fixed asset turnover and inventory turnover on Return on Assets (ROA) of pharmaceutical companies listed in Indonesia Stock Exchange in the period of 2012-2016. The research is used a quantitative research approach. This type of research was a descriptive study. The nature of this research is an explanatory research. The research populations were 9 pharmaceutical companies listed in Indonesia Stock Exchange in the period of 2012-2016. The research samples were 6 pharmaceutical companies listed in Indonesia Stock Exchange in the period of 2012-2016. The research data were analyzed using multiple regression analysis consiting of classical assumption tests including the tests of normality, multicollinearity, autocorrelation and heteroscedasticity. The research findings revealed that working capital turnover has a significant effect on Return on Assets (ROA) of pharmaceutical companies listed in Indonesia Stock Exchange in the period of 2012-2016. Fixed asset turnover has a significant effect on Return on Assets (ROA) of pharmaceutical companies listed in Indonesia Stock Exchange in the period of 2012-2016. Inventory turnover does not have any significant effect on Return on Assets (ROA) of pharmaceutical companies listed in Indonesia Stock Exchange in the period of 2012-2016. Simultaneously, working capital turnover, fixed asset turnover and inventory turnover have a significant effect on Return on Assets (ROA) of pharmaceutical companies listed in Indonesia Stock Exchange in the period of 2012-2016. Keywords : Working Capital Turnover, Fixed Asset Turnover, Inventory Turnover and Return on Assets (ROA)